2022
DOI: 10.3390/jcm11030767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Toothpaste on the Surface Roughness of the Resin-Contained CAD/CAM Dental Materials: A Systematic Review

Abstract: Background: The purpose of this review is to describe the possible effect of toothbrushing on surface roughness of resin-contained CAD/CAM materials. Methods: Systematic literature search for articles published in peer-reviewed journals between January 2000 and February 2020 has been conducted, which evaluated the effect of brushing on surface roughness of resin-contained CAD/CAM dental materials. The research was conducted in Scopus, PubMed/Medline, Web of Science, Embase, and Science Direct using a combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Despite this, the toothbrushing procedure itself caused a significant increase in the surface roughness because of the abrasive motion of the brushing process, simulating the environment inside the patient’s oral cavity. Toothpaste and toothbrush bristles might cause the abrasion of the ceramic surfaces by creating minor superficial grooves, and this observation is consistent with other studies [ 37 , 40 , 41 ]. The Ra readings of all the tested materials in all the subgroups of ceramic thicknesses exceeded 0.2 μm, which is considered to be the plaque accumulation threshold and, thus, roughness can be easily detected by the tongue and can lead to irritation and bacterial colonization [ 45 , 48 , 54 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Despite this, the toothbrushing procedure itself caused a significant increase in the surface roughness because of the abrasive motion of the brushing process, simulating the environment inside the patient’s oral cavity. Toothpaste and toothbrush bristles might cause the abrasion of the ceramic surfaces by creating minor superficial grooves, and this observation is consistent with other studies [ 37 , 40 , 41 ]. The Ra readings of all the tested materials in all the subgroups of ceramic thicknesses exceeded 0.2 μm, which is considered to be the plaque accumulation threshold and, thus, roughness can be easily detected by the tongue and can lead to irritation and bacterial colonization [ 45 , 48 , 54 ].…”
Section: Discussionsupporting
confidence: 92%
“…Surface roughness is one of the factors that influence the clinical survival of ceramics, since it might result in the wear and abrasion of the ceramics, crack initiation that can lead to fracture and staining, a loss of translucency, and bacterial colonization [ 34 , 35 , 36 , 37 ]. Previous studies have reported that the surface roughness threshold should be less than 0.2 µm in order to avoid plaque accumulation and bacterial adhesion on prosthetic materials [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tooth brushing is considered an effective method for preserving a good oral health environment. Unfortunately, it leads to loss of restoration gloss and an increase in surface roughness with subsequently plaque accumulation and deterioration of the mechanical properties 18,20,21 . Achieving good oral hygiene is affected by patient education, the complexity of restorations, and the dexterity of the patient 22 .…”
Section: Discussionmentioning
confidence: 99%